Zooplankton variability in the subtropical estuarine system of Paranaguá Bay, Brazil, in 2012 and 2013. (5th December 2017) - Salvador, Bianca; Bersano, José Guilherme F.
Abstract: Spatial and temporal dynamics of zooplankton assemblages were studied in the Paranaguá Estuarine System (southern Brazil), including data from the summer (rainy) and winter (dry) periods of 2012 and 2013. Zooplankton and environmental data were collected at 37 stations along the estuary and examined by multivariate methods. The results indicated significantly distinct assemblages; differences in abundance were the major source of variability, mainly over the temporal scale. The highest abundances were observed during rainy periods, especially in 2012, when the mean density reached 16378 ind.m −3 . Winter assemblages showed lower densities but higher species diversity, due to the more extensive intrusion of coastal waters. Of the 14 taxonomic groups recorded, Copepoda was the most abundant and diverse (92% of total abundance and 22 species identified). The coastal copepods Acartia lilljeborgi (44%) and Oithona hebes (26%) were the most important species in both abundance and frequency, followed by the estuarine Pseudodiaptomus acutus and the neritic Temora turbinata . The results indicated strong influences of environmental parameters on the community structure, especially in response to seasonal variations. The spatial distribution of species was probably determined mainly by their preferences and tolerances for specific salinity conditions. On the other hand, the abundances were strongly related to higher water temperature and precipitation rates, which can drive nutrient inputs and consequently food supply in the system, due to intense continental drainage.